The Implementation of SSCS (Search, Solve, Create, Share) Learning Model in training Students' Critical Thinking Skills - Risyda Hayati; Ahmad Fauzan Hidayatullah (Bioeducation Journal, 2022)
21st century learning emphasizes students' competence in finding out from a variety of sources, formulating problems, thinking analytically, working together, and collaborating on problem solving. Critical thinking skills are one of the skills that need to be developed in the 21st century. These skills can be trained in the learning process through one of the learning models, namely SSCS (Search, Solve, Create, Share) learning model. SSCS is one of the learning models that received a Grant to be developed and applied to mathematics and science subjects. This study aims to explain the implementation of SSCS learning model in training students' critical thinking skills. This research procedure uses library research method by collecting data in the form of articles published in various scientific journals and some from book sources. The result of the literature study about using the SSCS learning model that can have a positive impact for students that are more effective learning and training critical thinking skills for students.